PROSPECTS OF APPLICATION OF THE CONCEPTOF QUICK RESPONSE MANUFACTURING AT THE RUSSIAN INDUSTRIAL ENTERPRISES - Ch. V. Shipilova; I. A. Surov (Модернизация, инновация, развитие, 2016)
This article is devoted to research of such concept of the organization of production, as Quick Response Manufacturing or Quick-response production, at the center which, time of implementation of the order is put. Today domestic producers are compelled to function in new conditions, competing with a great number of players of the global market, as a result the emphasis on timely implementation of orders and a tendency of reduction of time of production will allow to reach competitive advantages. Fundamental aspects of Quick Response Manufacturing within functioning of the enterprise of branch are considered, and also the essential lack of this concept is revealed.The purpose / objectives. The purpose of article is research of the economic contents of the concept of the organization of production Quick Response Manufacturing and area of its use at the modern industrial enterprises. Article tasks: to investigate economic contents of the concept of Quick Response Manufacturing, to reveal its features and scopes in the modern industry.Methods. A methodical basis of this article are comparative methods of the analysis.Results. The economic contents of the concept of Quick Response Manufacturing are investigated. Four main key aspects which are the cornerstone of this concept are investigated: time force, organizational structure of the enterprise, system dynamics and possibilities of its application in scales of all enterprise. Components of positive work of system dynamics of the industrial enterprise are revealed, the trend of critical process of production is built. Considering that modern conditions demand from the enterprises to react, adapt quickly for the changing conditions, the factor of time plays an important role. Therefore the concept of QRM has rather perspective character, focusing attention on time of implementation of the order, in that communication that this parameter is one of key both for the enterprise, and for increase of its competitiveness.Conclusions and Relevance. It is necessary to expand practical use of instruments of controlling in activity of the industrial enterprises as they allow to increase management efficiency as a result of the accounting of opportunities and threats of environment and current state of the enterprise, its strong and weaknesses. Practical application of results of this work will allow to improve procedures of functioning of the industrial enterprises taking into account current economic and social trends.